The pieces of summer - Brunstetter, Wanda E. (Brunstetter, Wanda E. Discovery, 2013)
Meredith Stoltzfus could never love anyone like she loved her husband, Luke. When a friend from her past stops by her home to offer a helping hand, Meredith hesitantly agrees. But deep down, she feels uneasy about it. How would it look to others, seeing Jonah around so often?